2006
DOI: 10.1038/msb4100108
|View full text |Cite
|
Sign up to set email alerts
|

Long‐range signaling by phosphoprotein waves arising from bistability in protein kinase cascades

Abstract: A hallmark of protein kinase/phosphatase cascades, including mitogen-activated protein kinase (MAPK) pathways, is the spatial separation of their components within cells. The top-level kinase, MAP3K, is phosphorylated at the cell membrane, and cytoplasmic kinases at sequential downstream levels (MAP2K and MAPK) spread the signal to distant targets. Given measured protein diffusivity and phosphatase activities, signal propagation by diffusion would result in a steep decline of MAP2K activity and low bisphosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 30 publications
0
84
0
Order By: Relevance
“…This termination of signaling by phosphatases necessitates mechanisms to facilitate signal propagation across a cell. In fact, recent experimental and theoretical work showed that endocytosis, scaffolding, molecular motors, and traveling waves of phospho-proteins are involved in the propagation of signals to different cellular locations [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…This termination of signaling by phosphatases necessitates mechanisms to facilitate signal propagation across a cell. In fact, recent experimental and theoretical work showed that endocytosis, scaffolding, molecular motors, and traveling waves of phospho-proteins are involved in the propagation of signals to different cellular locations [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In reality, however, the signaling behavior is highly complex (Oda and Kitano, 2006) due to the dynamical interaction of the various intracellular molecules and pathways. To approach the non-intuitive character of signaling pathways, we therefore require systematic methodologies that incorporate both biological and theoretical methods to interpret signaling dynamics (Gilchrist et al, 2006;Markevich et al, 2006;Selvarajoo, 2006;Alon, 2007;Basak et al, 2007;Kholodenko, 2007). Recently, there have been such attempts to understand the signaling dynamics of TLRs (Covert et al, 2005;Selvarajoo, 2006).…”
Section: Systems Biology Approach To Tlr4 Signalingmentioning
confidence: 99%
“…This lack of temporal resolution prevented to investigate whether mitochondrial permeabilization is subject to spatial coordination by processes such as localized production of signaling molecules and/or diffusion, which were previously described as important regulators of other cellular signaling pathways, such as the forwarding of phosphorylation signals and Ca 2 þ waves. [15][16][17] We here describe a novel approach combining rapid cellular imaging and computational modeling to remedy this limitation in the analysis of apoptotic signaling. Taking advantage of the synchrony of sibling cells in apoptosis onset, we established an imaging technique that is capable of predicting the time of MOMP for individual cells with high probability.…”
mentioning
confidence: 99%